Revealing Chemopreventive Potential of Active Constituents from Medicinal Herbs Used in Indonesia for (Metastatic) Breast Cancer with Particular Molecular Targets - Indrasetiawan, Puguh; Haryanti, Sari; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2020)
Breast cancer remains as one of the highest causes of cancer-related deaths in the world, including Indonesia. In spite of following the standard protocol therapy, some patients in developing countries consume medicinal herbs as an alternative, complementary, as well as supportive therapies. Several herbs have been recognized to be used for this purpose. Annona muricata, Curcuma longa, Curcuma zanthorrhiza, Curcuma zedoaria, Phyllanthus urinaria, Gynura procumbens, Garcinia mangostana, Morinda citrifolia, and Nigella sativa are some of the plants used as chemopreventive agents with several formulas. Various types of extracts of Annona muricata show anticancer activities in vitro and in vivo. Curcumin, obtained from Curcuma longa and Curcuma zanthorrhiza, acts as p53 regulator and pro-oxidant in MCF-7 cells and also acts as a fatty acid synthase inhibitor in MDA-MB-231 cells. Xanthorrhizol from Curcuma zanthorrhiza has pro-apoptotic activity via modulation of Bcl-2, p53, and PARP-1 protein levels. Curcuma zedoaria contains curcumenone, curcumenol and curdion, which show pro-apoptotic activity in various cell lines and a cancer-induced mouse model. Corilagin and geraniin from Phyllanthus urinaria have different pro-apoptotic effects, in which, the corilagin-caused apoptotic effect is mediated by extrinsic and mitochondrial pathways, whereas geraniin induces apoptosis via ROS-mediated stimulation, both in MCF-7 cells. Thymoquinone from Nigella sativa has been extensively studied for its anticancer activities in recent years. Plants are cultivated, collected and mixed depending on the use as herbal medicines. Active compounds might be formulated if deemed possible. The development of more potential derivatives is also necessary to produce more optimum anti-cancer agents. In conclusion, Indonesian plants and their active constituents show potential activities to be developed as chemopreventive agents.Keywords: Indonesian medicinal herbs, breast cancer, active constituents, molecular targets